1995
DOI: 10.1523/jneurosci.15-07-05098.1995
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the nitric oxide/cGMP/cGMP-dependent protein kinase cascade in the induction of cerebellar long-term depression in culture

Abstract: Ms. Dorit Gurfel provi ded skillful technical assistance. Dr. T. Wal seth synthesized cADPr and 8-NH,-cADPr and kindly provi ded them for this investigation. Drs. U. Walter and P. De Camilli generously donated antiserum to PKG. Drs. S. Vincent and T. Wal seth provi ded useful comments on an earlier version of this manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
68
0
3

Year Published

1997
1997
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(77 citation statements)
references
References 37 publications
6
68
0
3
Order By: Relevance
“…However, these studies indicating a role for NO in hippocampal long-term potentiation Madison, 1991, 1994;Zhuo et al, 1994a,b) and hippocampal long-term depression (LTD) (Son et al, 1998) remain controversial (Selig et al, 1996). Similarly, it has been suggested that NO is critically involved in cerebellar LTD (Hartell, 1994(Hartell, , 2001Lev-Ram et al, 1995Boxall and Garthwaite, 1996), although this remains in debate (Linden et al, 1995). The present study proposes an alternative role for NO in influencing neural activity.…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies indicating a role for NO in hippocampal long-term potentiation Madison, 1991, 1994;Zhuo et al, 1994a,b) and hippocampal long-term depression (LTD) (Son et al, 1998) remain controversial (Selig et al, 1996). Similarly, it has been suggested that NO is critically involved in cerebellar LTD (Hartell, 1994(Hartell, , 2001Lev-Ram et al, 1995Boxall and Garthwaite, 1996), although this remains in debate (Linden et al, 1995). The present study proposes an alternative role for NO in influencing neural activity.…”
Section: Discussionmentioning
confidence: 99%
“…Cold Spring Harbor Laboratory Press on May 10, 2018 -Published by learnmem.cshlp.org Downloaded from receptors in response to paired glutamate application and depolarization regardless of whether or not the mice had nNOS (Linden et al 1995). It remains tmclear how and why cultured PCs should develop or unmask an independent biochemical cascade to respond to conjunctive extracellular and intracellular stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…The only previous test of nNOS deletion on cerebellar neurons was by Linden et al (1995), who cultured PCs from embryonic knockout mice and found no deficit in their ability to desensitize in response to simultaneous glutamate application and depolarization. This result confirmed their extensive previous data (including the lack of effect of NO donors or NOS inhibitors) showing that NO is not essential for LTD in cultured PCs (Linden and Connor 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in intact heart cells have yielded results consistent with a role for endogenous cADPR in the regulation of excitation-contraction coupling. In guinea pig cardiac myocytes stimulated to fire action potentials, Ca 2ϩ transients and contractions are enhanced by intracellular applications of cADPR (12) and reduced by antagonists of cADPR, 8-amino-cADPR and 8-bromo-cADPR (12)(13)(14)(15)(16)(17). These observations are consistent with endogenous cADPR, acting to enhance the Ca 2ϩ sensitivity of CICR, an action that may be antagonized by 8-amino-cADPR and 8-bromo-cADPR.…”
Section: Oscillations Of Camentioning
confidence: 99%